Regulatory divergence in Drosophila revealed by mRNA-seq - McManus, C. Joel; Coolon, Joseph D.; Duff, Michael O.; Eipper-Mains, Jodi; Graveley, Brenton R.; Wittkopp, Patricia J. (Genome research, 2010)
The regulation of gene expression is critical for organismal function and is an important source of phenotypic diversity between species. Understanding the genetic and molecular mechanisms responsible for regulatory divergence is therefore expected to provide insight into evolutionary change. Using deep sequencing, we quantified total and allele-specific mRNA expression levels genome-wide in two closely related Drosophila species ( D. melanogaster and D. sechellia ) and their F 1 hybrids. We show that 78% of expressed genes have divergent expression between species, and that cis - and trans -regulatory divergence affects 51% and 66% of expressed genes, respectively, with 35% of genes showing evidence of both. This is a relatively larger contribution of trans -regulatory divergence than was expected based on prior studies, and may result from the unique demographic history of D. sechellia . Genes with antagonistic cis - and trans -regulatory changes were more likely to be misexpressed in hybrids, consistent with the idea that such regulatory changes contribute to hybrid incompatibilities. In addition, cis -regulatory differences contributed more to divergent expression of genes that showed additive rather than nonadditive inheritance. A correlation between sequence similarity and the conservation of cis -regulatory activity was also observed that appears to be a general feature of regulatory evolution. Finally, we examined regulatory divergence that may have contributed to the evolution of a specific trait—divergent feeding behavior in D. sechellia . Overall, this study illustrates the power of mRNA sequencing for investigating regulatory evolution, provides novel insight into the evolution of gene expression in Drosophila , and reveals general trends that are likely to extend to other species.